Perfil de salud y tipo de contratación de académicos universitarios durante la pandemia por COVID-19 - Elvia Ortiz-Ortiz; Jeimy Marina Segura-Payán; Alba Mónica Montiel-González; Arturo Estrada-Torres; Amado I. Grandes-Blanco; Esmeralda García-Torres (REVISTA BIOMÉDICA, 2026)
Introduction: Employment status has been associated with declining health among university faculty, especially in crisis contexts such as the COVID-19 pandemic. Objective: To evaluate the association between employment status and health profile, as well as the risk of COVID-19 infection, among faculty members at the Autonomous University of Tlaxcala during the pandemic. Materials and methods: A descriptive, cross-sectional study was conducted between February and April 2022 with a convenience sample of 1,645 faculty members from the Autonomous University of Tlaxcala. A questionnaire, validated by experts, was used to collect sociodemographic and health data, differentiating between employment statuses (full-time vs. part-time). Associations between variables were analyzed using chi-square tests and adjusted residuals. A binary logistic regression model was fitted to control for confounding variables. Results: Full-time teachers had a higher frequency of chronic degenerative diseases than part-time teachers. Logistic regression confirmed that employment status was significantly associated with the risk of COVID-19 infection (OR = 0.667, 95% CI: 0.51–0.873, p = 0.0031), after controlling for age, sex, and the presence of chronic degenerative diseases. The presence of chronic degenerative diseases was the strongest predictor (OR = 1.576, 95% CI: 1.108–2.219, p = 0.0101). Conclusions: Employment type is associated with the health profile of university academics. Results should be interpreted with caution given the cross-sectional design and convenience sampling and cannot be generalized to the broader university teaching population.